2010
DOI: 10.1152/ajpendo.00541.2009
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of neuregulin as a modulator of muscle metabolism

Abstract: Gumà A, Martínez-Redondo V, López-Soldado I, Cantó C, Zorzano A. Emerging role of neuregulin as a modulator of muscle metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 91 publications
1
68
0
Order By: Relevance
“…Although most studies of NRG1 have focused on its myogenic and neurotrophic properties, it has been suggested that NRG1 can also influence glucose metabolism [5], particularly in skeletal muscle, the major site of insulin-stimulated glucose disposal. For instance, NRG1 increases glucose uptake in L6E9 myotubes and isolated strips of soleus muscle [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although most studies of NRG1 have focused on its myogenic and neurotrophic properties, it has been suggested that NRG1 can also influence glucose metabolism [5], particularly in skeletal muscle, the major site of insulin-stimulated glucose disposal. For instance, NRG1 increases glucose uptake in L6E9 myotubes and isolated strips of soleus muscle [9].…”
Section: Introductionmentioning
confidence: 99%
“…Neuregulin-1 (NRG-1) was initially described as a neurotrophic factor involved in neuromuscular junction formation in skeletal muscle, but recently it has emerged as a myokine, with relevant effects on myogenesis, muscle metabolism and regeneration, and has been considered as a strong candidate to transduce muscle adaptation to chronic exercise (Lebrasseur et al 2003;Guma et al 2010). …”
Section: Electrical Stimulation Induces Calcium-dependent Up-regulatimentioning
confidence: 99%
“…NRG 1 binds to tyrosine kinase receptors ErbB3 and ErbB4, which form homodimers or ErbB2 heterodimers. Dimerization induces ErbB receptor phosphorylation, activating a number of downstream intracellular signaling proteins via multiple mechanisms including PI3K-Akt and MAPK/ERK pathways (Carraway and Cantley, 1994, Yarden and Sliwkowski, 2001, Gumà et al, 2010). These signaling cascades affect transcription of a number of gene products that are essential for growth, differentiation and survival of the heart and nervous system (Falls, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to playing an important role in cardiac function, NRG 1β is involved in the regulation of glucose metabolism (Gumà, et al, 2010; Ennequin et al, 2015; Caillaud, et al, 2016). NRG 1β can influence glucose homeostasis through effects on the translocation of glucose transporters in rat L6E9 myoblasts (Suárez et al, 2001).…”
Section: Introductionmentioning
confidence: 99%